Discovery and Differential Processing of HLA Class II-Restricted Minor Histocompatibility Antigen LB-PIP4K2A-1S and Its Allelic Variant by Asparagine Endopeptidase - Kremer, Anita N.; Bausenwein, Judith; Lurvink, Ellie; Kremer, Andreas E.; Rutten, Caroline E.; van Bergen, Cornelis A. M.; Kretschmann, Sascha; van der Meijden, Edith; Honders, Maria W.; Mazzeo, Daniela; Watts, Colin; Mackensen, Andreas; et al. (Frontiers in Immunology, 2020)
Minor histocompatibility antigens are the main targets of donor-derived T-cells after allogeneic stem cell transplantation. Identification of these antigens and understanding their biology is a key requisite for more insight in how graft versus leukemia effect and graft versus host disease could be separated. We here identified 4 new HLA class II-restricted minor histocompatibility antigens using whole genome association scanning. For one of the new antigens, i.e. LB-PIP4K2A-1S, we measured strong T-cell recognition of the donor variant PIP4K2A-1N when pulsed as exogenous peptide, while the endogenously expressed variant in donor EBV-B cells was not recognized. We showed that lack of T-cell recognition was caused by intracellular cleavage by a protease named asparagine endopeptidase (AEP). Furthermore, microarray gene expression analysis showed that PIP4K2A and AEP are both ubiquitously expressed in a wide variety of healthy tissues, but that expression levels of AEP were lower in primary acute myeloid leukemia (AML). In line with that, we confirmed low activity of AEP in AML cells and demonstrated that HLA-DRB1*03:01 positive primary AML expressing LB-PIP4K2A-1S or its donor variant PIP4K2A-1N were both recognized by specific T-cells. In conclusion, LB-PIP4K2A-1S represents not only a novel minor histocompatibility antigen, but also provides evidence that donor T cells after allogeneic stem cell transplantation can target the autologous allelic variant as leukemia associated antigen. Furthermore, it demonstrates that endopeptidases can play a role in cell type-specific intracellular processing and presentation of HLA class II-restricted antigens, which may be explored in future immunotherapy of AML.